THE ROLE OF CORTICOSTEROID INJECTIONS IN SPORTS MEDICINE – ARTICLES REVIEW - Hubert Sawczuk; Katarzyna Pilarczyk; Aleksandra Rabęda; Marta Kaus; Zuzanna Cudziło; Weronika Ewa Nowak; Marta Malicka; Karina Grzesik; Hanna Adamska; Natalia Klepacz; Julia Marschollek (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: This article analyzes the use of corticosteroid injections in the treatment of various musculoskeletal injuries in athletes considering both benefits and risks. Efficacy of this kind of treatment was analyzed for most common injuries mentioned in the literature including: rotator cuff disorders, tendinopathy, carpal tunnel syndrome, tennis elbow, knee osteoarthritis, and femoroacetabular impingement (FAI) syndrome.Methodology: For the purpose of this article, databases such as PubMed, PMC, Google Scholar, and Scopus were searched for relevant documents.Results: Review of the literature shows differences between the outcomes in specific injuries, but most of them show effective short-term pain reduction with corticosteroid injections. It is important to drive extra attention to other forms of therapies such as physical therapy, which combined with steroid injections improve patient outcomes.